MULTI – HAZARD VULNERABILITY MAPPING: AN EXAMPLE OF AKWA IBOM STATE, NIGERIA - Udoh, Joseph C. (European Scientific Journal, ESJ, 2015)
Vulnerability mapping has emerged as one of the mitigation strategies in the midst of increasing losses due to environmental hazards in recent years. It generally improves the ability of policy makers to promote disaster reduction thereby protecting inhabitants and their livelihoods, the natural environment, infrastructure and property. Although vulnerability maps can be created manually, they are now mostly created with the assistance of computer technology called Geographic Information System (GIS). Mapping the vulnerability of the region in a GIS environment allows for ease of data editing, integration, analysis, storage and visualization. The resultant product will help to identify, and locate sensitive populations so that emergency managers can customize disaster relief efforts based on needs determined by the identified vulnerability. Vulnerability of the study area was conceptualized in a GIS environment as a combination of Exposure, Sensitivity, and Adaptive capacity maps. The three surfaces for each hazard were generated and combined using the Single Output function of Arcmap 9. The study area is Akwa Ibom State located in the South East Coast of Nigeria, an area prone to sea level rise, coastal erosion and flooding. The result shows that the high and moderate zones are concentrated in the North East and Southern parts of the state while the low zones can be found in the North West. As the state borders the Atlantic Ocean, the study confirms the fact that the southern parts of the state are highly vulnerable to climate change related hazards.